2018
DOI: 10.1016/j.hpb.2018.06.176
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after single port laparoscopic cholecystectomy: a randomized clinical trial

Abstract: Results: Preoperative characteristics of patients and disease were comparable between MILS and Open Group. Laparoscopic series resulted in a statistically significant lower blood loss (200 vs 350, p=0.03), minor intraoperative blood transfusions (3.2% vs 7.9%, p=0.04) and postoperative blood transfusions (10.5% vs 15.8%), other than shorter lenght of stay (4 vs 6 days, p=0.04). Number of retrieved nodes was 8 vs 7 (p=ns); particularly, percentage of patients who achieved the recommended AJCC cutoff of six lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It can also arise from objective reasons. For example, laparoscopy technology itself has certain limitations; when operations are performed on the screen, it is sometimes difficult to determine the accurate anatomical position, because the surgeon cannot directly touch the operation area; and obese patients will also affect the surgical field of vision to a certain extent [20][21][22]. In addition, changes in the shape and position of the gallbladder will increase the risk of BDI [23].…”
Section: Discussionmentioning
confidence: 99%
“…It can also arise from objective reasons. For example, laparoscopy technology itself has certain limitations; when operations are performed on the screen, it is sometimes difficult to determine the accurate anatomical position, because the surgeon cannot directly touch the operation area; and obese patients will also affect the surgical field of vision to a certain extent [20][21][22]. In addition, changes in the shape and position of the gallbladder will increase the risk of BDI [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, SILC has not gained widespread acceptance possibly because it is a more technically challenging operation than CLC [7,22]. Additionally, SILC has been associated with longer procedure times and more complications, without signifi cant benefi t in terms of patients' satisfaction, postoperative pain, and quality of life [7,19,22]. This was likely attributed to the technical diffi culties faced during the procedure which include instrument clashing, reduced visibility, and reduced mobility of instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that SILC offers better cosmesis, reduced postoperative pain, lesser complications and faster recovery time compared to CLC [4,[10][11][12]. However, SILC has not gained widespread acceptance due to increased operative time (57.8mins versus 35.2mins), technical diffi culty, minimal cosmetic benefi t and analgesia benefi t, and increased incisional hernia rates (13.3% versus 4.7%) [4,7,9,10,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%